1996
DOI: 10.1183/09031936.96.09122590
|View full text |Cite
|
Sign up to set email alerts
|

Low intensity peripheral muscle conditioning improves exercise tolerance and breathlessness in COPD

Abstract: L Lo ow w i in nt te en ns si it ty y p pe er ri ip ph he er ra al l m mu us sc cl le e c co on nd di it ti io on ni in ng g i im mp pr ro ov ve es s e ex xe er rc ci is se e t to ol le er ra an nc ce e a an nd d b br re ea at th hl le es ss sn ne es ss s i in n C CO OP PD D ABSTRACT: This randomized, controlled study investigated the physiological effects of a specially designed 12 week programme of isolated conditioning of peripheral skeletal muscle groups. The programme required minimal infrastructure in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
2
8

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(96 citation statements)
references
References 13 publications
5
81
2
8
Order By: Relevance
“…Both groups had significant improvement in Saint George's Respiratory Questionnaire score (see Table 4). This is in accordance with previous studies, which also found improved health-related quality of life and dyspnea after either high-intensity 2,28,32 or lowintensity exercise training [5][6][7]27 . Although the enduranceand-strength group had a greater improvement in Saint George's Respiratory Questionnaire score, this difference was not significant, compared to the improvement in the calisthenics-and-breathing group (see Table 4).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both groups had significant improvement in Saint George's Respiratory Questionnaire score (see Table 4). This is in accordance with previous studies, which also found improved health-related quality of life and dyspnea after either high-intensity 2,28,32 or lowintensity exercise training [5][6][7]27 . Although the enduranceand-strength group had a greater improvement in Saint George's Respiratory Questionnaire score, this difference was not significant, compared to the improvement in the calisthenics-and-breathing group (see Table 4).…”
Section: Discussionsupporting
confidence: 82%
“…2,4 Programs that include high-intensity exercise (such as endurance and strength training) and lowintensity training (such as callisthenic exercises in the sitting and standing position, moving the upper limbs against gravity) improve outcomes that are relevant to patients (eg, overall dyspnea, functional performance, and health status). 2,[5][6][7] On the other hand, high-intensity programs tend to result in deeper physiological improvements, being especially efficient in increasing exercise capacity and muscle force. 2 However, an important issue not yet investigated is whether different exercise training programs result in different post-program effects on the level of physical activity in daily life in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Given that deconditioning is one of the principal causes of muscle dysfunction, exercise training is a logical step to improve physical performance. The role of exercise training in pulmonary rehabilitation is well established and is known to improve exercise capacity and health status in patients with chronic lung disease [7,8]. These improvements are partly due to metabolic adaptations in the peripheral muscles.…”
mentioning
confidence: 99%
“…Duas intensidades de treinamento de força são apresentadas na literatura: o treinamento de moderada a alta intensidade baseado em intensidades relativas (50-90%) de uma repetição máxima (maior quantidade de carga que pode ser mobilizada em uma amplitude total de determinado movimento -1RM) (2,19,20) (Tabela 1), e o treinamento com pesos leves ou com a própria resistência dos segmentos corporais (21)(22)(23)(24) (Tabela 2). A Tabela 3 apresenta os delineamentos e resultados dos principais ensaios clínicos envolvendo pacientes com DPOC.…”
Section: Treinamento De Força Isoladounclassified
“…Os autores atribuíram tais resultados ao fato de que o exercício de pressão das pernas exige atividade significativa dos músculos abdominais, os quais são fundamentais para a expiração forçada (20) . Quanto ao treinamento de baixa intensidade, Clark et al (21) avaliaram os efeitos do treinamento em 48 pacientes com DPOC randomizados em grupo de treinamento ou grupo controle não exercitado. O grupo de treinamento foi submetido a seqüência de exercícios isoinerciais durante 12 semanas (2x/semana) (Tabela 2), o qual mostrou melhora significativa da força e resistência musculares e do tempo de endurance em esteira rolante.…”
Section: Treinamento De Força Isoladounclassified